Edukasi Kelompok Lansia dalam Menjaga Kualitas Kesehatan Personal di Desa Borisallo, Kec. Parangloe, Kab. Gowa - Sri Julyani; Nasruddin Syam; Nurfachanti Fattah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The elderly group (elderly), aged 60-69 years, is part of the community that is vulnerable to various health problems, both physically, mentally, and socially. Untreated health problems can reduce the quality of life and become a burden for individuals and society. In Borisallo Village, Parangloe District, Gowa Regency, there are around 320 elderly residents. Through the Community Service (PKM) program of the Fostered Village in collaboration with the Borisallo Village Government and funded by the UMI Endowment Foundation, a series of activities were carried out to improve the quality of personal health of the elderly. The activity was carried out in November 2024 at the Borisallo Village Hall and included two main forms, namely: (1) elderly health checks covering blood glucose, cholesterol, uric acid, blood pressure, body temperature, and weight; and (2) counseling on the importance of maintaining overall health quality. Although only 15 participants registered for the counseling, the number of participants who attended exceeded expectations, indicating high enthusiasm from the community. The results of the examination showed that some elderly people required medical follow-up for further treatment. The program also emphasizes the importance of regular and continuous monitoring of the health of the elderly so that their condition can be monitored objectively and early intervention can be carried out. The activity took place in an atmosphere full of empathy, care, and a spirit of service that respects and loves the elderly.